A systematic literature review to understand the difference between critical factors affecting the national election and state elections in India - Chatterjee, Joydeep; Dutta, Gautam (Frontiers in Political Science, 2024)
This study aims to understand the dominant factors of political marketing, to influence voters, in respect to national and state elections of India. To identify the same, we have reviewed literature of different nations (both developed and developing) across the world and India. We have defined specific criteria and search terms to first identify the relevant studies which has discussed about influencing factors in global and Indian political marketing landscape. Once identified, we found out key takeaways, in terms of finding the influencing factors, of all those studies and discussed the different emerging trends of shifting power from party brand to leadership brand in national election. We have also analyzed impact of different factors like party leader or candidate's personality, party policy and ideology, use of social media as campaigning tool, campaign messaging and platform, on national and state elections over the years. We found that for national election, partly leadership and use of social media are critical factors, while for state election party policy and ideology with on ground campaigns still affect significantly.